An Early Iron Age cup with unique decoration from Fertőrákos (NW Hungary) - Attila Mrenka (Dissertationes Archaeologicae: Ex Instituto Archaeologico Universitatis de Rolando Eötvös Nominatae)
The Early Iron Age cemetery at Fertőrákos-Kőhidai dűlő is one of the best-known sites in the vicinity of Sopron. Excavations took place there in 1970, but the material was published only in 2009. During the nearly four decades inbetween, heritage management was reorganised several times, and the excavated material was divided between two separate museums, so reuniting it required a small-scale revision, including a reevaluation of the record. The aim of this article is to present the unique painted decoration of an Early Iron Age cup.